Alton B. Parker papers - Parker, Alton B. (Alton Brooks), 1852-1926.
Correspondence, speeches, legal opinions, autobiographical and biographical studies, financial records, printed matter, scrapbooks, photographs, and other papers primarily concerning the presidential election of 1904 in which Parker ran as the candidate of the Democratic Party and his work with legal, civic, and philanthropic organizations. Organizations include the Albany Law School, American Bar Association, American Committee for Armenian Independence, Charity Organization Society of the City of New York's Committee on Criminal Courts, English Speaking Union of the United States, Lawyers' Club (New York, N.Y.), National Civic Federation, National Council of Religion in Higher Education, New York State Bar Association, Sulgrave Institution of the United States and of the British Commonwealth, and the Thomas Jefferson Memorial Foundation, Inc. Correspondents include Josephus Daniels, Ralph M. Easley, Rufus Wheeler Peckham, and William H. Taft.
Lawyer, judge, and Democratic presidential candidate.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Daniels, Josephus, -- 1862-1948 -- Correspondence; Easley, Ralph M. -- 1858- -- Correspondence; Peckham, Rufus Wheeler, -- 1838-1909 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Albany Law School; American Committee for Armenian Independence; American Bar Association; Charity Organization Society of the City of New York. -- Committee on Criminal Courts; Democratic Party (U.S.); English-Speaking Union of the United States; Lawyers' Club (New York, N.Y.); National Civic Federation; National Council of Religion in Higher Education; New York State Bar Association; Sulgrave Institution of the United States and of the British Commonwealth; Thomas Jefferson Memorial Foundation, Inc; Charities; Civic improvement -- Societies, etc; Elections -- United States -- 1904.; Law -- Societies, etc; Presidents -- United States -- Election -- 1904.; United States -- Politics and government -- 1901-1909.; Jurists; Lawyers